Hubungan Antara Kebiasaan Merokok, Aktivitas Fisik, Riwayat Keluarga Dengan Kejadian Hipertensi Di Wilayah Kerja Puskesmas Nguter - Suprihatin, Anggun; , Bejo Raharjo, SKM, M.Kes; , Anisa Catur Wijayanti, SKM, M.Epid (2016)
Hypertention is a degenerative disease that became one cause of death in the world. This is evident from the data of WHO (2014), which explained that the increase in blood pressure is a major risk factor for global mortality and is estimated to have caused 9,4 milion deaths. In Indonesia, the number of hipertensive patients estimated 15 million people but only 4% which is controlled hipertensive patients.the purpose of this study was to determine the relationship of smoking habits, physical activity, family history of hypertension in the region of Nguter Health.This research method using analytical design with case control approach , the technique of random sampling cluster sampling in which a total population 85 of respondent and 51 samples of respondents with a ratio of case and control 1:1. Distribution of smoking habit as many as 18 people (17.6 %) , lack of physical activity as much as 7 (13.7%) and had a history of hypertension, a family of 25 people (49%) .Statistical test using Chi Square. The results showed no association between smoking (p=0,603; OR=0,763; 95%CI=0,274-2,123) , physical activity (p=0,160; OR=3,898; 95%CI=0,769-19,761) and there is a relationship between family history (p=0,008; OR=0,296; 95%CI=0,127-0,691) with hypertension in Nguter Health.